At the intersection: Race, gender, and discretion in police traffic stop outcomes. (July 2022) - Roach, Kevin; Baumgartner, Frank R.; Christiani, Leah; Epp, Derek A.; Shoub, Kelsey
Abstract: Racial disparities in traffic stop outcomes are widespread and well documented. Less well understood is how racial disparities may be amplified or muted in different contexts. Here we focus on one such situational factor: whether the initial traffic stop was related to a traffic safety violation or a (broadly defined) investigatory purpose. This is a salient contextual characteristic as stop type relates to different levels of assumed discretion and purpose. While all traffic stops involve some officer discretion, investigatory stops are more easily used as justifications to conduct a search based on an officer's diffuse suspicion; traffic safety stops are more often just what they seem. Using millions of traffic stops from several states, we show that black male drivers are more likely to be searched and less likely to be found with contraband and that this relationship is amplified where the initial stop purpose is investigatory. One implication of this is that one path to alleviating disparities in traffic stops for agencies is emphasizing traffic safety, rather than using stops as a supplemental investigatory tool.